Burkholderia phytofirmans Inoculation-Induced Changes on the Shoot Cell Anatomy and Iron Accumulation Reveal Novel Components of Arabidopsis-Endophyte Interaction that Can Benefit Downstream Biomass Deconstruction - Zhao, Shuai; Wei, Hui; Lin, Chien-Yuan; Zeng, Yining; Tucker, Melvin P.; Himmel, Michael E.; Ding, Shi-You (Frontiers in Plant Science, 2016)
It is known that plant growth promoting bacteria (PGPB) elicit positive effects on plant growth and biomass yield. However, the actual mechanism behind the plant-PGPB interaction is poorly understood, and the literature is scarce regarding the thermochemical pretreatability and enzymatic degradability of biomass derived from PGPB-inoculated plants. Most recent transcriptional analyses of PGPB strain Burkholderia phytofirmans PsJN inoculating potato in literature and Arabidopsis in our present study have revealed the expression of genes for ferritin and the biosynthesis and transport of siderophores (i.e. the molecules with high affinity for iron), respectively. The expression of such genes in the shoots of PsJN-inoculated plants prompted us to propose that PsJN-inoculation can improve the host plant’s iron uptake and accumulation, which facilitates the downstream plant biomass pretreatment and conversion to simple sugars. In this study, we employed B. phytofirmans PsJN to inoculate the Arabidopsis thaliana plants, and conducted the first investigation for its effects on the biomass yield, the anatomical organization of stems, the iron accumulation, and the pretreatment and enzymatic hydrolysis of harvested biomass. The results showed that the strain PsJN stimulated plant growth in the earlier period of plant development and enlarged the cell size of stem piths, and it also indeed enhanced the essential metals uptake and accumulation in host plants. Moreover, we found that the PsJN-inoculated plant biomass released more glucose and xylose after hot water pretreatment and subsequent co-saccharification, which provided a novel insight into development of lignocellulosic biofuels from renewable biomass resources.